(untitled) (Desarrollo, Estado y Espacio, 2023)
The present paper seeks to analyze whether the trajectories of urban social policies which agree with the human rights-based approach —participative, comprehensive and progressive— make those policies more likely to become a counterbalance to territorial inequalities and a progress on rights expansion, and, vice versa, whether the shortfalls in the operationalization of these principles negatively affect their possibilities of transforming the processes of accumulation of disadvantages in territory. The city of Rosario (Argentina) has been a remarkable example on this matter as it has implemented innovative policies which seek to adopt a human rights-based approach. Therefore, this article intends, firstly, to analyze the institutionalization trajectories of the socio-urban integration policies implemented in the city of Rosario since the beginning of the century. Secondly, it analyzes the implementation of those policies in the "Cullen" area inside the neighborhood of Empalme Graneros in Rosario over the 2014-2022 period. The methodology is qualitative and uses secondary sources (documentary information, evaluation and research) and primary sources which include in-depth interviews with 16 key actors (government officials and State workers, social organizations and territorial leaders from the neighborhood). The analysis of a specific neighborhood shows positive transformations, as they are appreciated by neighborhood inhabitants, but they are also perceived as insufficient or unfinished due to coordination difficulties and to fluctuations or “interruptions” in the trajectories of policy institutionalization, which negatively affect incipient transformations in the face of urban inequalities which, far from being reduced, are larger and more complex.